THE VERTICAL ANDEAN CHALLENGE . CHALLENGES OF GRAVITY IN PRECOLONIAL ANDEAN SOCIETIES - Bolaños, Aldo (2010)
The author proposes in the present paper a different look from the Andean space, a integrated perspective with the geography and his landscape environments. Endorsed by the archaeological and historical information in topics as the architecture, the agriculture and the same cultural landscape, the author raises an integrated and alternative understanding of the andean societies precoloniales focused in alternatives of development, finally calling the attention of the risks and threats that nowadays presents the cultural heritage of the region.